Advanced 3D woven profile structures and their composites for automotive applications. Issue 9 (29th July 2022) - Behera, Bijoya Kumar; Kamble, Zunjarrao
Abstract: The woven profiled structures and their composites are beneficial for automobiles specifically E‐vehicles due to near‐net‐shape manufacturing, snug‐fitting, and lightweight. This study reported the junction strength of 3D integrally woven, and stitched profile structures such as L, U, +, ±, T, Pi, and H produced using high‐strength polyester yarn and their composites. The junction strength of integrally woven profiles and their composites was higher than that of stitched profiles. The stitched profile composites failed at the stitch line mainly due to delamination, leading to incomplete reinforcement strength realization. However, the integrally woven profile composites fail due to fracture of yarns within the reinforcement, leading to higher junction strength. Abstract : The boltless composite joining is one of the important challenges in the aerospace and automotive industry. The conventional techniques of joining namely bolting, adhesive bonding, and stitched profile composites lack in integrity of the joining. The 3D profile weaving enables manufacturing of products modularly to achieve savings in manufacturing costs, effort, and time and improve performance and reliability. The integrally woven profile structural composites have higher junction strength compared to stitched profile composites.